Micro-Entrepreneur: Motivations, Challenges and Success Factors - Kalimah, Shahidan (2011)
Micro-enterprise plays an important role in contributing toward a stable and sustainable social and economic community environment. A core of small enterprise, particularly micro-enterprise (five or fewer employees), is needed to build and maintain the sustainability of social cultural, environment and economic development of communities. The purpose of this study is to examine the motivations, challenges and key success factors for micro-entrepreneur in Kedah and Perlis. The micro-entrepreneur reveals that they are motivated to increase their income at the time they entering their business. Manage the business well and customer services as the key of success factors in their business. More than that, scarcity of financial resources in their business is a challenge to them.